221 Effects of energy drinks on inflammatory response: study in vivo in rats. (8th December 2021) - Gaetano, Anna De; Zanini, Giada; Selleri, Valentina; Malerba, Mara; Manenti, Antonio; Farinetti, Alberto; Caramaschi, Stefania; Bonetti, Luca Reggiani; Pinti, Marcello; Nasi, Milena; Mattioli, Anna Vittoria
Abstract: In recent years, the consumption of energy drinks (EDs) has increased constantly among young people because of their capacity to enhance alertness and improve mental and physical performance, reducing fatigue. EDs are beverages containing a high and variable amount of caffeine, which exerts effects on many tissues of the cardiovascular system. In addition to caffeine, they contain several other psychoactive substances including the amino acid taurine, the glucose derivative glucuronolactone, as well as herbal extracts such as guaranà (another source of caffeine, with caffeine-like effects) and ginseng, often present in not well-known concentration. In our project we aim to evaluate whether the consumption of EDs causes alterations in the organs involved in their contact, absorption and metabolism in an animal model, i.e. the rat. We used 28 Sprague Dawley adult male rats, weighing 230–250 g and fed with a standard laboratory diet, randomly divided into four groups ( N = 7). Every group received a different treatment (ED, soda-cola, sweetened coffee or water-controls-) for 5 days. All animals were anesthetized and underwent histological analysis and blood sampling at the end of the treatment. We observed eosinophilic infiltrates in gastrointestinal tract, but not in cardiovascular system. We quantified various indicators of tissue damage and cytokines in plasma, including ICAM-1, L-selectin, TIMP-1, VEGF, IL-10, IL-2, IL-4, IL-6, IL-1β, IL-13, IL-33, TNF-α, and IFN-γ. In contrast with the eosinophilic infiltration, we did not detect a systemic increase of Th2 cytokines (i.e. IL-4 and IL-13) after treatment: thus, even if the experiments evaluating the possible presence of an unbalanced Th2 response in the tissues featured by eosinophilic infiltration are still lacking, we exclude further deepening on Th2 immune responses. Interestingly, we observed a decrease of TIMP-1 in plasma from rats orally supplemented with ED, soda-cola or sweetened coffee compared to animals treated with water. TIMP-1 is a major player in preserving tissue integrity and controlling wound healing by balancing the enzymatic activity of matrix metalloproteinases (MMPs) and regulating extracellular matrix turnover. Moreover, elevated levels of the adhesion molecules ICAM-1 and L-selectin were found in plasma from rats receiving ED or soda-cola, together with a high concentration of IL-33 in animals assuming the ED. The circulating form of ICAM-1 is associated with inflammation, particularly due to endothelial damage, and L-selectin and IL-33 play an important role in inflammatory conditions as well. These observations suggest that the consumption of EDs could alter the architecture, and hence function, of the organs involved in their contact, absorption and metabolism. Indeed, the alterations we observed in the periphery could reflect the establishment of inflammation and deregulated mechanisms of damage repair locally in the target tissues.